Use Of Fiqh Rules In Majelis Permusyawaratan Ulama (MPU) Aceh Fatwa On Cigarette Law - Iskandar (Tunas Institute, 2024)
The issue of smoking law is not a new problem, there are many opinions of scholars regarding smoking law, some are pro and some are against. One of the fatwas regarding smoking is the fatwa issued by the Aceh MPU number 18 of 2014 concerning Smoking According to Islamic Views. In the fatwa issued by the Aceh MPU on December 3 2014, there are the first five points; Cigarettes are objects made from tobacco that contain nicotine. Second; The use of nicotine for a certain period of time can damage health, thirdly; Smoking for people who is prohibited by medical experts is Haram, fourth; Smoking with behavior that does not respect other people is Haram, fifth; Caregivers and educators who allow children to smoke are guilty. This research attempts to examine the Aceh mpu fatwa from the perspective of its legal basis. In determining smoking laws, the Aceh MPU uses the basis of the Qur'an, hadith, ijma', qiyas, the opinions of ulama, fiqhiyyah rules and ushuliyyah rules, and what is the focus of the study in this research is the use of fiqhiyyah rules used by the Aceh MPU in determining smoking law.